2017
DOI: 10.1007/s00404-017-4400-2
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-based endometrial cytology associated with curettage in the investigation of endometrial carcinoma in a population of 1987 women

Abstract: Liquid-based endometrial cytology can be considered a useful method for detecting of endometrial pathology as a first-line approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…13,29 Additionally, the monolayer preparation of the collected cells may allow for a more comprehensive assessment of the epithelium. 28,30 Previous studies have suggested the Tao brush method as an attractive alternative to endometrial biopsy as it is just as minimally invasive but less uncomfortable 15,20 and more cost effective. 20 The Tao brush cytology specimen is processed in a very similar manner to cervical cytology, which has been an established diagnostic method for several decades.…”
Section: Discussionmentioning
confidence: 99%
“…13,29 Additionally, the monolayer preparation of the collected cells may allow for a more comprehensive assessment of the epithelium. 28,30 Previous studies have suggested the Tao brush method as an attractive alternative to endometrial biopsy as it is just as minimally invasive but less uncomfortable 15,20 and more cost effective. 20 The Tao brush cytology specimen is processed in a very similar manner to cervical cytology, which has been an established diagnostic method for several decades.…”
Section: Discussionmentioning
confidence: 99%
“…Such high‐risk women are defined as those attending routine cervical screening who are nulligravid or postmenopausal and report abnormal bleeding in the past 6 months 58 . Endometrial cytology requires uterine instrumentation and is therefore less acceptable as a screening tool; however, it is associated with much lower rates of inadequate/failed sampling than endometrial biopsy 59 . Screen‐detected endometrial cancers are also identified at an earlier stage and boast improved survival outcomes compared with women diagnosed following acute symptomatic presentation 58 …”
Section: Screening For Endometrial Cancermentioning
confidence: 99%
“…This makes liquid-based endometrial cytology, which prepares samples for cytology examination by depositing the collected sample into a preservative liquid, a useful method for detecting endometrial pathologies as a first-line approach compared to the more invasive, painful and expensive endometrial biopsy, D&C and hysteroscopy. Cytology sampling performed by brushing the uterus cavity followed by a liquid-based smear has demonstrated an optimal diagnostic accuracy [23]. …”
Section: Liquid Biopsy In Endometrial Cancermentioning
confidence: 99%